Activated PPARγ Targets Surface and Intracellular Signals That Inhibit the Proliferation of Lung Carcinoma Cells. (15th July 2008) - Han, Shou Wei; Roman, Jesse
Abstract : Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the nuclear hormone receptor superfamily. Their discovery in the 1990s provided insights into the cellular mechanisms involved in the control of energy homeostasis, the regulation of cell differentiation, proliferation, and apoptosis, and the modulation of important biological and pathological processes related to inflammation and cancer biology, among others. Since then, PPARs have become an exciting target for the development of therapies directed at many disorders including cancer. PPARs are expressed in many tumors including lung cancer, and their function has been linked to the process of carcinogenesis. Consequently, intense research is being conducted in this area with the hope of discovering new PPAR-related therapeutic targets for the treatment of lung cancer. This review summarizes the research being conducted in this area, and focuses on the mechanisms by which a member of this family (PPARγ ) is believed to affect lung tumor cell biology.